2002
DOI: 10.1159/000067197
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Epithelium of the Vaginal Complex during the Estrous Cycle of the Marsupial <i>Monodelphis domestica</i>

Abstract: The vaginal complex of marsupials differs from that of eutherians. Cervices open separately in a sinus vaginalis or cul-de-sac. Two lateral vaginae adjoin the sinus vaginalis and fuse at the level of the urethra opening and form the sinus urogenitalis. During the estrous cycle the vaginal epithelium undergoes a number of specified morphological changes. This paper is the first to describe these changes on an ultrastructural level in a marsupial. Investigations in Monodelphis vagina reveal that a cyclic switch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 111 publications
3
17
0
1
Order By: Relevance
“…In M. domestica, vaginal epithelium changes during the estrous cycle have been analyzed by light and transmission electron microscopy [Regli and Kress, 2002]. In this scanning electron-microscopic study the same four stages of the estrous cycle will be characterized as in our previous transmission electron-microscopic paper, namely proestrus, estrus, postestrus and a transitional metestrus and the results will be correlated with the previous findings and possible functional implications.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In M. domestica, vaginal epithelium changes during the estrous cycle have been analyzed by light and transmission electron microscopy [Regli and Kress, 2002]. In this scanning electron-microscopic study the same four stages of the estrous cycle will be characterized as in our previous transmission electron-microscopic paper, namely proestrus, estrus, postestrus and a transitional metestrus and the results will be correlated with the previous findings and possible functional implications.…”
Section: Introductionmentioning
confidence: 84%
“…3a). The superficial layers are sometimes ortho-but mostly parakeratinized [Regli and Kress, 2002]. The transition from the highly keratinized epithelium of the sinus vaginalis to the columnar cervical epithelium is abrupt ( fig.…”
Section: Estrusmentioning
confidence: 99%
See 2 more Smart Citations
“…The period of increased CEC, dictated by elevated E 2 concentrations, which results in proliferation and desquamation of vaginal epithelial cells, was used in the present study to designate cytological estrus (de Brux 1958, Regli & Kress 2002. The use of monitoring CEC in S. crassicaudata has been broadly described by Godfrey (1969), Godfrey & Crowcroft (1971) and Bennett et al (1979) who reported estrus and mating at times of increased CEC.…”
Section: Cec Monitoringmentioning
confidence: 99%